An Entrepreneur‘s Character from Professor Musa Asy'arie's Perspective - Hizbul Khootimah Azzaakiyyah (Apollo: Journal of Tourism and Business, 2023)
The unpredictable development of the times has made many people look for solutions in order to have a provision for the future through the role of entrepreneurs. However, not a few of them are still not stable in understanding what the real business goals are for, and what characteristics an entrepreneur must have in order not to take the wrong steps and directions. Thus, this study aims to present the ideal character that can be applied to an entrepreneur. This research includes literature research, because the research was conducted to find, analyze, make interpretations and generalizations from the facts of the thoughts and ideas written by Musa Asy'arie regarding the character of an entrepreneur. This research is descriptive qualitative with a secondary data analysis approach. The results of this study indicate that there are nine ideal characteristics of an entrepreneur. The conclusion from these various characteristics is that an entrepreneur is also a thinker by nature. The results of the thought process must better understand the essence and existence of an entrepreneur, be able to create creative solutions in problem solving and stand the test. That is, for an entrepreneur profit is not always the main orientation, because this is the result of the effect created. This effect must be based on the essence and existence of an entrepreneur as a goal of worship in their entrepreneurial dimension. This study can be used as a formal reference or reference in the academic realm in the field of entrepreneurship